2017
DOI: 10.1016/j.hpb.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring future liver remnant function prior to hepatectomy may guide the indication for portal vein occlusion and avoid posthepatectomy liver failure: a prospective interventional study

Abstract: A predefined cutoff for preoperatively calculated eFLRF can be used as a tool for selecting patients prior to hepatectomy, with or without PVO, thus avoiding PHLF and PHLF-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Five studies reported historical comparisons on the outcome rate of LF and mortality in the period before and after implementation of nuclear imaging as a preoperative examination in patients undergoing liver surgery [ 16 , 20 , 25 , 56 , 58 ]. Overall, the historical comparisons involving [ 99m Tc]Tc-mebrofenin found that implementation of nuclear imaging in the preoperative assessment resulted in lower mortality and liver failure rates [ 16 , 20 , 25 ], whereas the historical comparisons on the use of [ 99m Tc]Tc-GSA did not result in a significant decrease in the number of liver failure cases in the period after implementation of [ 99m Tc]Tc-GSA liver scintigraphy [ 56 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies reported historical comparisons on the outcome rate of LF and mortality in the period before and after implementation of nuclear imaging as a preoperative examination in patients undergoing liver surgery [ 16 , 20 , 25 , 56 , 58 ]. Overall, the historical comparisons involving [ 99m Tc]Tc-mebrofenin found that implementation of nuclear imaging in the preoperative assessment resulted in lower mortality and liver failure rates [ 16 , 20 , 25 ], whereas the historical comparisons on the use of [ 99m Tc]Tc-GSA did not result in a significant decrease in the number of liver failure cases in the period after implementation of [ 99m Tc]Tc-GSA liver scintigraphy [ 56 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported historical comparisons on the outcome rate of LF and mortality in the period before and [16,20,25], whereas the historical comparisons on the use of [ 99m Tc]Tc-GSA did not result in a significant decrease in the number of liver failure cases in the period after implementation of [ 99m Tc]Tc-GSA liver scintigraphy [56,58].…”
Section: Historical Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective interventional study investigated management strategy to avoid PHLF in 100 patients. [ 41 ] eFRL-F cutoff of 2.3%/min/m 2 as described by Chapelle et al . [ 35 ] was used to decide management.…”
Section: Resultsmentioning
confidence: 99%
“…91,92 One of the strategies used to prevent this syndrome is portal vein embolization 4 to 6 weeks prior to hepatectomy, which gives time for the perfused segments of the liver to undergo hypertrophy, effectively increasing the functional liver remnant at the time of hepatectomy. 93,94 Naturally, a prerequisite for this approach is a capable interventional radiology (IR) department working in coordination with the hepatobiliary surgeon. Another option to prevent this has been explored in experimental settings, where a portocaval shunt at the time of resection decreased sinusoidal edema and improved survival.…”
Section: Surgical Portosystemic Shunts In Liver Resectionsmentioning
confidence: 99%